CO2 zero schools: school building renovation towards emissions neutrality - Almeida, Manuela Guedes de (2015)
Vila Nova de Gaia, a 300.000 inhabitants municipality in Portugal, has established the goal of transforming their schools into carbon emissions free buildings. The first pilot project shows a combination of cost effective energy efficiency measures with renewable energy harvesting allowing reducing nearly 90% final energy use and carbon emissions.